2022
DOI: 10.1038/s41467-022-33992-5
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional reduction and incommensurate dynamic correlations in the $$S=\frac{1}{2}$$ triangular-lattice antiferromagnet Ca3ReO5Cl2

Abstract: The observation of spinon excitations in the $$S=\frac{1}{2}$$ S = 1 2 triangular antiferromagnet Ca3ReO5Cl2 reveals a quasi-one-dimensional (1D) nature of magnetic correlations, in spite of the nominally 2D magnetic structure. This phenomenon is known as frustration-induced dimensional reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…It is interesting to note that similar mechanisms have also been proposed for the origin of quantum disorder in spin liquids. 61–80…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that similar mechanisms have also been proposed for the origin of quantum disorder in spin liquids. 61–80…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that similar mechanisms have also been proposed for the origin of quantum disorder in spin liquids. [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] We found that disordered phases with weak short-range correlations produce structure factors that are similar to those of long range spin state ordered phases, which can complicate their experimental identification. Diffuse scattering is only observed when strong short-range correlations are present.…”
Section: Discussionmentioning
confidence: 99%
“…Recent high-field ESR measurements have revealed that the spiral magnetic order in CROC is stabilized by uniform DMIs. 51 Because the incommensurate magnetic order stabilized by DMIs is expected to host interesting phenomena such as magnetoelectric effects and magnetic skyrmions, the spiral magnetic order in CROC has garnered interest.…”
Section: Discussionmentioning
confidence: 99%
“…Another pair of orbital lobes (blue in Figure 3b) is arranged in a staggered manner between adjacent chains with a smaller overlap, resulting in the weak interchain exchange of J′. According to first-principles calculations and subsequent highfield ESR experiments, the J′/J anisotropies were estimated to be 0.295 19 and 0.254, 51 respectively. It should be noted that the direct exchange interactions are sufficiently large even though the transition metals are separated from each other by more than 5 Å.…”
Section: Anisotropic Interactionmentioning
confidence: 99%